Credentials, talent and cultural capital: a comparative study of educational elites in England and France. Issue 2 (17th February 2016) - Brown, Phillip; Power, Sally; Tholen, Gerbrand; Allouch, Annabelle
Abstract : This article examines student accounts of credentials, talent and academic success, against a backdrop of the enduring liberal ideal of an education-based meritocracy. The article also examines Bourdieu's account of academic qualifications as the dominant source of institutionalised cultural capital, and concludes that it does not adequately account for comparative differences in the social structure of competition and ideological shifts in class (re)production in different national contexts. This analysis is based on an empirical investigation of elite students at Oxford University and Sciences Po in Paris. We investigated how they understand the competition for a livelihood and whether they see themselves as more 'talented' than students from non-elite universities. This investigation revealed important similarities and differences between British and French students that have significant sociological implications for the (re)production and legitimation of educational and labour market inequalities.